Kekerasan Simbolik Negara Atas Nama Food Estate Dalam Konteks Demokrasi - Uli Arta Trisnawati (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study reveals symbolic violence perpetrated by the state in the name of food estates. Several theories used to examine the forms of symbolic violence that occurred include Pierre Bourdieu's theory of symbolic violence and Jurgen Habermas's theory of deliberative democracy. The study employed qualitative methods. The results revealed two forms of violence perpetrated by the state: psychological violence, and symbolic violence. In food estate programs and policies, symbolic violence operates through inequality in the relationship between the community as the controlled party, the state as the party that controls the community but is also controlled by companies, and companies as the party that controls the government, resulting in food estate programs and policies that have proven to fail repeatedly. In fact, legal regulations were created to accommodate the food estate program. In the context of democratizing livelihoods, the food estate program, from the era of President Soeharto to President Jokowi, represents a dismal reflection of democracy in Indonesia. The lack of public space is characterized by the absence of dialogue between citizens and state administrators in choosing methods for protecting and managing food resources. Deliberative democracy must be the government's path to addressing Indonesia's food crisis and ending the symbolic violence perpetrated in the name of food estates. At the same time, actions must be taken to overthrow the dominant discourse (Doxa) regarding food estates by adopting a new discourse (Heterodoxa) based on local knowledge and traditional practices. This new discourse must be able to fill the public space, which must be guaranteed by the government.